Ex-situ soil washing of diesel contaminated soil using impinging stream reactors and selective soft self attrition - Mare, Pieter Willem (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Ing.) -- University of Stellenbosch, 1999.